PENGARUH KINERJA PEGAWAI, PENGAWASAN MELEKAT DAN PENGAWASAN FUNGSIONAL TERHADAP EFEKTIFITAS PENGELOLAAN KEUANGAN DAERAH ( Studi Empiris Pada SKPD Provinsi Riau ) - Wiguna, Meilda; ', Nurhanifah; ', Desmiyawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Financial management of local government is essentially the entire area activities including planning, administration, reporting, accountability, and oversight of local government finances. This study aims to determine the effect of Employee Performance, Embedded Control and Functional Control Towards The Effectiveness of The Financial Management of Local Government at SKPD Riau Province as the research object. Respondents in this study were 97 echelon III and IV. The type of data used is primary data by using questionnaire method of data collection. The method of data analysis used in this study is multiple regression with the help of SPSS software version 19.0. The results of this study show, both partial and simultaneous variable of employee performance, embedded control and functional control significant positive effect on the effectiveness of the financial management area. While the coefficient of determination shows all independent variables used in this study provide a contribution of 39 % of the dependent variable. While the remaining 61 % describe other independent variables that are not observed in this study.Keywords : employee performance, embedded control, functional control, the effectiveness of the financial management area